2020
DOI: 10.1186/s12966-020-0912-4
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ and toddlers’ physical activity and sedentary time as measured by accelerometry: a systematic review and meta-analysis

Abstract: Background: Early experiences in physical activity (PA) are important to shape healthy movement behaviours long-term; as such, it is critical that PA is promoted from infancy, and that detrimental behaviours (e.g., prolonged sedentary time [ST]) are minimized. The purpose of this systematic review and meta-analysis was to examine infants' and toddlers' movement behaviours across daytime hours. Methods: Seven online databases were searched for terms related to infants (< 12 months), toddlers (12-35.9 months), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 68 publications
1
45
0
3
Order By: Relevance
“…There were several limitations. First, while the accelerometer sub-sample was larger than most other accelerometer studies with young children [ 71 , 72 ], the sample was nonetheless small and the wide confidence intervals signify that the target parameters could be quite different from the point estimates. We also fitted 54 models in total, which meant that was substantial opportunity for spurious results.…”
Section: Discussionmentioning
confidence: 99%
“…There were several limitations. First, while the accelerometer sub-sample was larger than most other accelerometer studies with young children [ 71 , 72 ], the sample was nonetheless small and the wide confidence intervals signify that the target parameters could be quite different from the point estimates. We also fitted 54 models in total, which meant that was substantial opportunity for spurious results.…”
Section: Discussionmentioning
confidence: 99%
“…Classifying body position from wearable sensors provides a third option that addresses the limitations of both video and survey methods. Lightweight inertial movement units (IMUs)small sensors that contain an accelerometer and gyroscope-can be worn for the entire day or multiple days taped to the skin, embedded in clothing, or worn on a wristwatch (Cliff et al, 2009;de Barbaro, 2019;Lobo et al, 2019;Bruijns et al, 2020). Notably, an experimenter does need not to be present, and data can be recorded at a dense sampling rate in real time.…”
Section: Introductionmentioning
confidence: 99%
“…Such issues have been previously highlighted by Henriksson et al ., 24 who found limited availability of easy‐to‐use, validated methods to assess physical activity in the early years. A recent systematic review found that, overall, young children tend to exceed the physical activity recommendations; however, very little of this time is spent at higher intensities 25 . Throughout the LEAF interventions, the whole family were encouraged to gradually increase the time spent on them, as well as the intensity and the range of physical activities that they engaged in.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that, overall, young children tend to exceed the physical activity recommendations; however, very little of this time is spent at higher intensities. 25 Throughout the LEAF interventions, the whole family were encouraged to gradually increase the time spent on them, as well as the intensity and the range of physical activities that they engaged in.…”
Section: Discussionmentioning
confidence: 99%